2020
DOI: 10.1007/s40615-020-00923-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Social Determinants Past, Present, and Future, and African Americans’ Health

Abstract: As the COVID-19 pandemic progresses, more African Americans than whites are falling ill and dying from the virus and more are losing livelihoods from the accompanying recession. The virus thereby exploits structural disadvantages, rooted partly in historical and contemporary anti-Black sentiments, working against African Americans. These include higher rates of comorbid illness and more limited health care access, higher rates of disadvantageous labor market positioning and community and housing conditions, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 46 publications
2
78
0
1
Order By: Relevance
“…It is apparent that COVID-19 has exacerbated health inequality and reduced life expectancy in the USA [ 31 , 34 ]. This study has shown the disparity in COVID-19 case fatality ratio, and it aligns with other studies situated within the social determinant of health framework, as shown in the literature [ 17 , 18 , 48 ]. According to the World Health Organization [ 49 ], the social determinant of health suggests that race/ethnicity, power, and location determine health outcomes for an individual or a group of people.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is apparent that COVID-19 has exacerbated health inequality and reduced life expectancy in the USA [ 31 , 34 ]. This study has shown the disparity in COVID-19 case fatality ratio, and it aligns with other studies situated within the social determinant of health framework, as shown in the literature [ 17 , 18 , 48 ]. According to the World Health Organization [ 49 ], the social determinant of health suggests that race/ethnicity, power, and location determine health outcomes for an individual or a group of people.…”
Section: Discussionsupporting
confidence: 90%
“…For example, African Americans have intergenerational poverty, which reflects in their health conditions [ 50 ]. In the pre-pandemic, African Americans and Hispanics had the least access to health care in the USA due to their inability to access health insurance principally because of low income [ 18 ]. Our study further provides evidence of health disparity by race/ethnicity and by place of residence, corroborating studies on racial and ethnic health disparity in the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), disproportionately affects the elderly, African Americans, those with obesity, and institutionalized individuals (nursing home residents) ( 5 , 6 ), all of which are also identified as a high-risk population for vitamin D deficiency ( 2 , 3 , 4 , 7 ). This association could potentially contribute to higher COVID-19 morbidity and mortality rates appreciated in this population.…”
Section: Introductionmentioning
confidence: 99%
“…As such, future models would do well to incorporate information on the varied population densities within correctional housing spaces to better understand viral spread. Another important characteristic that future models should consider is the disproportional impact of the pandemic on minorities (25,26) . To elaborate, Blacks and Hispanics are overrepresented by 5.6 and 3.0 times more than White adults (22) in U.S. correctional facilities, which contributes to disparities of these groups in COVID-19 testing, cases, and deaths.…”
Section: Resultsmentioning
confidence: 99%